2021
DOI: 10.1016/j.breast.2021.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of PARP inhibitors in patients with BRCA-mutated advanced breast cancer: A meta-analysis and systematic review

Abstract: Objective This meta-analysis aimed to investigate the efficacy and safety of poly (adenosine diphosphate-ribose) polymerase (PARP) inhibitors in BRCA- mutated advanced breast cancer patients comprehensively. Methods We conducted a systematic literature research through PubMed, the Cochrane Central Register of Controlled Trials (CENTRAL), Embase, China National Knowledge Infrastructure (CNKI), wanfang, China Biology Medicine disc (CBMdisc), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…In addition, our meta-analysis also evaluated the e cacy of PARPis in combination with chemotherapeutic agents. Although OS and ORR did not improve, PFS had signi cant bene ts (HR 0.71 [95%CI, 0.59 to 0.85], p = 0.00002), which is consistent with the strati ed results of our PARPis combination therapy (43). Meanwhile, our analysis also noted that there was no signi cant difference in bene t between monotherapy and combination therapy, which may provide strong evidence for future clinical drug combination.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, our meta-analysis also evaluated the e cacy of PARPis in combination with chemotherapeutic agents. Although OS and ORR did not improve, PFS had signi cant bene ts (HR 0.71 [95%CI, 0.59 to 0.85], p = 0.00002), which is consistent with the strati ed results of our PARPis combination therapy (43). Meanwhile, our analysis also noted that there was no signi cant difference in bene t between monotherapy and combination therapy, which may provide strong evidence for future clinical drug combination.…”
Section: Discussionsupporting
confidence: 87%
“…A subanalysis of their data confirmed these positive results for both BRCA1-mutant carriers (HR 0.65; 95% CI: 0.53–0.78) and BRCA2-mutant carriers (HR 0.63; 95% CI: 0.51–0.76) as well as for triple-negative cases (HR 0.62; 95% CI: 0.50–0.77). Further to this, Sun et al [ 39 ] showed that progression-free survival significantly improved using the single-agent PARP inhibitor in BRCA1 patients (HR 0.64; 95% CI: 0.53–0.79) with similar results in triple-negative breast cancer patients (HR 0.65; 95% CI: 0.54–0.79). These researchers also reported adverse hematological events: neutropenia in 35% of the patients studied, anemia in 29%, and thrombocytopenia in 24%.…”
Section: Parp Inhibitors For Treatment Of Breast Cancermentioning
confidence: 88%
“…In a recent meta-analysis [ 74 ], PARP inhibitors were found to prolong progression-free and overall survival in patients with BRCA mutations and advanced breast cancers, with tolerable safety and overall improved quality of life. In breast cancers, two PARP inhibitors, olaparib and talazoparib, were recently approved in germline BRCA mutation (gBRCAm ) carriers for the treatment of metastatic HER2-negative breast cancer based on both the OlympiAD [ 75 ] and EMBRACA [ 76 ] trials, respectively.…”
Section: Homologous Recombinationmentioning
confidence: 99%